Temporal distribution of non-methane hydrocarbon (NMHC) in a developing equatorial island - Al Madhoun, W. A. (Springer Netherlands, 2016)
Non-methane hydrocarbons (NMHC) play a vital role in the formation of ozone in urban environment, where vehicle emissions are dominant. Ozone is known for its negative impacts on human health and environment. This study examines the prevalence of NMHC using central fitting distribution for equatorial area of Penang Island, Malaysia. The results of the diurnal variations of the NMHC concentrations measured during the years 2005 and 2006 showed that the concentrations were varying over the 24-h period while peaking from 8:00 to 10:00 am. In 2006, the maximum concentration of NMHC at the island station was 0.30 ppm, and the minimum level was 0.15 ppm. In term of probability distribution, the NMHC concentrations surrounding the station were well represented by Weibull distribution in 2005 and lognormal distribution in 2006 with an accuracy of 99.6 and 99.4 %, respectively. Moreover, the predicted number of days exceeds the US standard for NMHC (0.24 ppm) were 107 days. The Pearson’s correlation analysis showed a significant correlation (average r > 0.85) between NMHC concentrations and the measured CO emissions which indicate that they have a common source which is vehicular emissions. The factor analysis results showed that the temperature and humidity were the main contributors to the variance of NMHC concentrations. This study suggests that a special attention should be taken into consideration because of the potential health threat posed to the human.